2020
DOI: 10.1136/bmjopen-2019-034079
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and mothers’ knowledge, attitude and practice towards glucose-6-phosphate dehydrogenase deficiency among neonates with jaundice: a cross-sectional study

Abstract: BackgroundNeonatal jaundice (NNJ) is a frequent complication of glucose-6-phosphate dehydrogenase (G6PD) deficiency.ObjectivesTo estimate the prevalence of G6PD deficiency among neonates with jaundice and to assess mothers’ perception towards G6PD and NNJ.MethodsA cross-sectional study was carried out on 487 ethnic Egyptian neonates with indirect hyperbilirubinaemia from June 2018 to July 2019. The collected data included maternal and neonatal characteristics. Laboratory investigations included serum bilirubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
6
20
1
Order By: Relevance
“…In this study, 45.4% of mothers had good knowledge about neonatal jaundice. This knowledge level was better than that reported in other countries such as Nepal 23 (22%), Egypt 24 (30%) and Karbala city, Iraq 25 (34%). This may be attributed to the high proportion (83.1%) of our respondents who had graduated from university.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In this study, 45.4% of mothers had good knowledge about neonatal jaundice. This knowledge level was better than that reported in other countries such as Nepal 23 (22%), Egypt 24 (30%) and Karbala city, Iraq 25 (34%). This may be attributed to the high proportion (83.1%) of our respondents who had graduated from university.…”
Section: Discussioncontrasting
confidence: 69%
“…Our study also found that education level was significantly associated with knowledge about neonatal jaundice, which was consistent with the results of an earlier review. 26 Due to differences in scoring algorithms or items investigating attitudes and practices, [23][24][25] it was difficult to compare attitudes and behaviours reported in our study with those from other countries. The majority (80.6%) of participants in this study had received prior health education on neonatal jaundice, which suggested that their knowledge about neonatal jaundice would be high.…”
Section: Discussionmentioning
confidence: 93%
“…Several authors have found that the prevalence of G6PDd is higher in jaundiced newborns than in the control population, ranging from 8.9 to 28.1% [26][27][28][29][30] (Table 3). Even some individuals carrying the hypomorphic G6PD A− 202A/376G haplotype had enzymatic values that were close to the cutoff value (5.3 U/g Hb, 4.6 and 4.8 U/g Hb in the groups with and without NNJ, respectively), while other individuals showed extremely low enzymatic values (1.1 U/g Hb and 1.4 U/g Hb in the NNJ and without NNJ groups, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have found that the prevalence of G6PDd is higher in jaundiced newborns than in the control population, ranging from 8.9 to 28.1% [26][27][28][29][30]. Badejoko G6PDd families with more than one affected patient (Table 4), in which only two patients had antecedent NNJ and one of them had a hemyzygous G6PD A− 202A/376G genotype (class III) experienced two episodes of AHA at the ages of 9 and 24 months old, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most of them stated that ascorbic acid, aspirin, and probenecid 80%, 66%, and 74% respectively as medications that can be used with caution in G6PD deficient patients. [2,4,5,16,18] . Most of the current study participants aged 25-34 years, this explains why 44% were senior pharmacist i.e.…”
Section: Participants' Demographic Datamentioning
confidence: 99%